William Blackstone, 1 Commentaries on the Laws of England 104 (1847) - (:unkn) unknown (My University, 1765)
Discussed "the fifth and last auxiliary right", that Englishmen shall have arms for their defence. "Suitable to their condition and degree, and such as are allowed by law.
Keywords: GUARANTEED RIGHT